Active defense technology against intelligent jammer - Zhibin FENG; Yuhua XU; Zhiyong DU; Xin LIU; Wen LI; Hao HAN; Xiaobo ZHANG (Tongxin xuebao)
In the complex electromagnetic countermeasure environment, the intelligent development of jammer has caused a serious threat to wireless communication, while the traditional anti-jamming methods often passively adjusted the working mode or parameters, which will be at a disadvantage or even suppressed in the face of intelligent jammer.To solve this problem, a technical framework of active defense against jammer was proposed, aiming to disrupt the learning process of the intelligent jammer and reduce the jamming efficacy.In order to gradually achieve the goals of “understanding opponent”“controlling opponent” and “defeating opponent”, under the guidance of game theory and adversarial machine learning, the key technologies were discussed from three aspects: backward reasoning of jammer, algorithm vulnerability analysis and confrontational strategy design, independent optimization and online decision-making of anti-jamming strategy.Finally, combined with two specific cases, the feasibility and effectiveness of the proposed technical framework were verified.